The role of parents in teaching the Environmental Concepts to Child Of Kindergartens "Afield Study on Kindergartens in Tartous City" - Mortuada , ٍSalwa; Shaheen , Yousef (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
. This research aims to definition the environmental concepts to child of kindergartens, and The role of parents in teaching the environmental concepts to child of kindergartens in Tartous City, also tries to identify the differences in their opinions based on the following variables: (sex, certificate). To achieve the objectives of the research, the Author designed a questionnaire consisting of (52) items, divided into four fields.This instrument was, then administered to a sample of (308) persons during the 2016-2017 first Term. The results of the questionnaire were analyzed, using the mathematical averages, relative weights, Cronbach's Alpha equation, Spearman, Brown & Gotmann's Coefficients, T-Test, One Way ANOVA and LSD. To validate the instrument, it was presented to a panel of seven (7) specialists in Tishreen and Tartous Universities. The instrument was validated by pilot administration to a random sample of fifty (22) persons (a = 0.97, p = 0.98). The research results showed that the role of parents in teaching the environmental concepts to child of kindergartens in Tartous City were a medium degree, as it was shown that there were no differences of statistical indication about the role of the parents in teaching the Environmental Concepts to Child of Kindergartens according to the sex, whereas statistical indicating differences were shown regarding the different according to scientism certificate in favor of the higher certificate, The research also provided suggestions of interest in education Environmental and care of Children in Kindergartens and house.